An Analysis of Code-Mixing Used by the English Teachers - Agus Adi Guna, I Kadek (Universitas Pendidikan Ganesha, 2023)
The type of insertion code-mixing was the most dominant type used by students in communicating. This study aimed to analysing the types of code-mixing and the teachers’ reasons of code-switching used by the English teachers in teaching English. This study is a descriptive qualitative research. The subjects of this study are two English teachers who taught English subject. The teachers who teach in 10th and 11th grades of language major. The data were collected using two methods, such as observation and interview. The instruments used are video recorder, tape recorder, observations sheets, and interview guide. Researcher analyze the data, data collected will be transcribed into written form to facilitate classification. The transcribed data in script form will be analysing using Hoffman’s theory. The results showed that there are three types of code-mixing used by the English teachers. There are intra sentential code-mixing (62.1%), intra lexical code-mixing (18.7%), and involving a change in pronounciation (19.2%). Moreover there are total 198 utterances, which is of 49 utterances used because the students’ English ability are low, 33 utterances used to diagnosing students, 29 utterances used to get closer to the students, 16 utterances used to making a joke, and 71 utterances used because the habit factor.